Political discussions on admission of neutral countries of the Arctic region to NATO in the 1990s - 2000s: inclusion or a limited neutrality? - Boldyreva, Slavyana Yu.; Boldyrev, Roman Yu. (Vestnik Volgogradskogo gosudarstvennogo universiteta. Serija 4. Istorija. Regionovedenie. Mezhdunarodnye otnoshenija, 2019)
Sweden and Finland obtain a special position within NATO strategy towards neutral states. The purpose of the paper is to analyze the background and perspectives for Sweden and Finland to join NATO in the 1990s - 2000s. This issue appeared on the top of agenda after these countries had entered the EU, and right after the Baltic states became members of NATO. Finland started to distant itself from Russia in 1990-1992, right after recognizing itself free from military and technical limitations set in the Peace treaty signed in 1947 and gaining an ability to arrange political and military alliances with other countries. Joining the Alliance has first appeared on the Finnish political agenda in the first half of the 1990s, though the political elite of Finland defining its practical relations with NATO also took into consideration the position of Russia since both countries had a long joint terrestrial border and close economic relations. Sweden started revising its foreign policy vector in 1991. The governing elite had an active discussion which ended with a compromise decision on preserving the neutral status of the country alongside with enforcing its defensive capacities. Since 1992, Finland and Sweden became participants of various agreements with NATO. Their armed forces and armaments systems have adopted the NATO standards, and have been working out their practical interaction during the joint military maneuvers and within Partnership for Peace program. In 2009 Nordic defense cooperation emerged, including three NATO participants - Iceland, Norway and Denmark. In April 2014 they signed an agreement on close military cooperation. Results: We can state without any doubt that Finland and Sweden would join NATO only when they face a real threat towards themselves. Russian policy in the region can be a trigger for that. After Crimea annexed Russia, the amount of advocates of joining NATO increased. Nevertheless, they still remain a minority. In this situation a referendum on joining NATO appears to have no ...